Transitions, challenges and trends in China's abalone culture industry - Xiaolong Gao; Mo Zhang; Xuan Luo; Weiwei You; Caihuan Ke (Reviews in Aquaculture, 2023)
Abalone species are economically important shellfish in China's aquaculture industry. In 2020, China's abalone aquaculture production was 203,500 tonnes, accounting for nearly 90% of total global production. However, many problems have accompanied the rapid development of this industry, including a reduction in near‐shore space suitable for culture and the risk of exposure of farms to natural disasters such as typhoons and red tides. In addition, high temperatures and low oxygen levels resulting from global climate change are causing increased abalone mortality in summer. In this review, the culture patterns and characteristics used in different countries are compared with respect to larvae nurseries, intermediate juvenile culture and the grow‐out phase. Next, the transitions and challenges in China's abalone culture industry over the past 60 years are summarized. Finally, a coordinated land‐sea program for reducing solid waste emissions into the water and increasing carbon sinks is suggested based on the ‘Carbon Neutrality’ theory. Under the framework of the program, new facilities, technologies and models should be created to achieve increased mechanization and a greater understanding of the abalone aquaculture industry as soon as possible. This review provides references and data to support the scientific planning and mapping of China's abalone culture industry as well as the transition of China's perceived identity from a major fishery country to a strong fishery power with an awareness of environmental protection and resource use.